Preparation of alkali-activated steel slag-fly ash based full solid waste filling material and strength formation mechanism research - Tingye QI; Siyuan CHENG; Guorui FENG; Linfei WANG; Hongtao XU; Lubin LI; Xinkai QI; Kexin XU; Xingyue YANG (Meitan kexue jishu)
To utilize steel slag solid waste resources, this study developed a fully solid-waste-based cemented coal backfill material using alkali-activated steel slag-fly ash cementitious material as a cement substitute and coal gangue as aggregate. The effects of activator (Na2SiO3) modulus and alkali concentration on both macroscopic properties and microstructural evolution of the cementitious system were systematically investigated. Optimal parameters were applied to prepare backfill materials with varying steel slag contents, with reaction mechanisms elucidated through XRD, SEM, and FT-IR analyses. Experimental results demonstrated that a steel slag∶ fly ash ratio of 6∶4 yielded compressive strengths of 5.35 MPa (7-day) and 8.71 MPa (28-day), showing 62.8% strength enhancement. With optimized activator parameters (modulus=1.75, concentration=8% Na2O equivalent), the 28-day compressive strength reached 20.85 MPa. Microstructural characterization revealed that alkali activation facilitated mineral phase dissociation in steel slag and fly ash, releasing Ca, Al, and Si ions to form polymerized C−(A)−S−H gels through hydration. The optimal mixture (coal gangue∶steel slag∶fly ash∶water=5∶4∶1∶2) exhibited 7-day and 28-day compressive strengths of 1.80 MPa and 2.94 MPa, respectively. SEM-EDS analysis confirmed the formation of dense interfacial transition zones through surface reactions between coal gangue and cementitious matrix, effectively reducing porosity and enhancing aggregate bonding strength. This work establishes an efficient pathway for preparing low-carbon coal gangue backfill materials with high solid-waste incorporation, demonstrating significant potential for large-scale steel slag utilization in sustainable mine engineering applications.